Message Security Application Using Mobile-Based AES Algorithm - Rifki, Mhd Ikhsan; Syamia, Nanda (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2024)
All information in data exchange transactions on communication networks travels through the network infrastructure. The network infrastructure sends various types of data, including text, images, and documents with various extensions. These documents may be private and confidential. Therefore, it is crucial to have a message security option that is not only user-friendly but also has a high level of security system complexity. The purpose of this research is to build a text message security system using the Advanced Encryption Standard (AES) algorithm on mobile devices. We can utilize it as a security solution to safeguard text messages received through mobile devices. The AES security algorithm is known to have reliability in processing data encryption and decryption. The research will describe components such as the design, implementation, and analysis of application requirements. Important features include encryption, decryption, and key management in addition to an easy-to-use UI. The research findings show that this program successfully secures text messages while maintaining the confidentiality and integrity of the data sent. Additionally, we adjusted the application's parameters to align with mobile device standards, ensuring consistent encryption and decryption procedures that users can easily operate. For application testing, we use the black box testing method to ensure that the design and application function as intended, adhere to security regulations, and provide a positive user experience. This study's results suggest that AES-based mobile messaging security applications can serve as a tool to fulfill the secure communication expectations of mobile users.